2009
DOI: 10.7163/gpol.2009.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Extreme water level fluctuations along the Polish coast

Abstract: The paper examines annual extreme sea levels along the Polish Baltic coast. The analysis is based on water level data sets collected at gauging stations in Świnoujście, Kołobrzeg, Ustka, and Gdańsk in the years 1946-2001. The article also draws upon historical data. The results of the study show that differences between the maximum and minimum levels have increased, particularly during the last 50 years. Sea level amplitudes tend to be wider in the western part of the Baltic coast than in the eastern part. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…1.5–2.0 m above the average level. The historically noted maxima are 1.96 m above the mean sea-level at Świnoujście and 2.16 m at Kołobrzeg (Wiśniewski et al, 2009; Wolski et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…1.5–2.0 m above the average level. The historically noted maxima are 1.96 m above the mean sea-level at Świnoujście and 2.16 m at Kołobrzeg (Wiśniewski et al, 2009; Wolski et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…They were executed using the XBeach package for conditions of an event with the recurrence period of 20 years. Thus, following Boniecka et al (2013), the (peak) wave period was set at T = 8.5 s and the significant wave height at H s = 5.71 m. Next, following Wiśniewski et al (2009) the value of storm surge was set at 1.3 m, roughly corresponding to the return period of 20 years; the sea level rise effect was included by adding extra 0.7 m, jointly producing a storm lea level of 2 m above the current msl. Finally, following British Standard Code of practice for Maritime structures (2000) and Dnv-Os-J101 (2011), the duration of event was set at 3 h, i.e., the effects of storm peak were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the highest surge of 216 cm above msl in the entire history of mareographic records on the Polish coast was reported at Kołobrzeg, located between km 330 and 335 Figure 1A in 1874. Statistical analysis of this long series revealed that surges of 150 cm above msl can occur roughly every 10 years (Wiśniewski et al, 2009). As Kołobrzeg is located some 20 km west of Lake Jamno, it demonstrates that the barriers experience the impacts of high surges once per decade on average and this rate is expected to rise under climate change.…”
Section: Site Descriptionmentioning
confidence: 88%
See 1 more Smart Citation
“…The an nual re sul tant (net) long shore sed i ment trans port on the up per shoreface is ~111,000-145,000 m 3 /year, mov ing from west to east (Szmytkiewicz et al, 2021). Ac cord ing to the near est mareographic sta tions in £eba and W³adys³awowo, the max i mum wa ter level dur ing the mi gra tion of low air pres sure sys tems and as so ci ated storm surges can reach 1.68 m and 1.38 m above the av er age (Wioeniewski et al, 2009). Ac cord ing to the mareographic sta tion lo cated in W³adys³awowo (~10 km west of the study area), the av er age rate of sea level rise between 1951 and 2015 was 2.04 mm/year (Kowalczyk, 2019).…”
Section: Study Areamentioning
confidence: 98%